Synthetic bone marrow images augment real samples in developing acute myeloid leukemia microscopy classification models - Jan-Niklas Eckardt; Ishan Srivastava; Zizhe Wang; Susann Winter; Tim Schmittmann; Sebastian Riechert; Miriam Eva Helena Gediga; Anas Shekh Sulaiman; Martin M. K. Schneider; Freya Schulze; Christian Thiede; Katja Sockel; et al. (npj Digital Medicine)
Abstract High-quality image data is essential for training deep learning (DL) classifiers, yet data sharing is often limited by privacy concerns. We hypothesized that generative adversarial networks (GANs) could synthesize bone marrow smear (BMS) images suitable for classifier training. BMS from 1251 patients with acute myeloid leukemia (AML), 51 patients with acute promyelocytic leukemia (APL), and 236 stem cell donors were digitized, and synthetic images were generated using StyleGAN2-Ada. In a blinded visual Turing test, eight hematologists achieved 63% accuracy in identifying synthetic images, confirming high image quality. DL classifiers trained on real data achieved AUROCs of 0.99 across AML, APL, and donor classifications, with performance remaining above 0.95 even when incrementally substituting real data for synthetic samples. Adding synthetic data to real training data offered performance gains for an exceptionally rare disease (APL). Our study demonstrates the usability of synthetic BMS data for training highly accurate image classifiers in microscopy.